Exploring the relationships between the gut microbiome composition and movement patterns of laying hens in a multitier cage-free housing system - Anaïs Cazals; Sabine Gebhardt-Henrich; Quentin Berger; Marie-Noëlle Rossignol; Deborah Jardet; Michael J. Toscano; Tatiana Zerjal (PLoS ONE, 2026)
In this study we investigated the relation between caecal microbiota composition and movement patterns in laying hens. We used hens from Pure line matings of Hendrix Genetics to continuously monitor the movement of individuals in a connected three-tier aviary throughout the laying period, from 18 to 60 weeks of age. The aviary contained three vertical tiers: a top-level, mid-level, and lower-level. In addition, the aviary had a floor littered and an attached wintergarden which was accessible from approximately 21 WOA onwards. Differences in the hens’ use of space were observed including: differences in the number of visits and time spent in the wintergarden and litter areas. Microbiota characterization, using 16S rRNA gene sequencing from 237 samples, revealed an association (P < 0.05) between microbiome composition and the number of visits to the litter. We observed differences (adjusted P-value < 0.05) between hens that frequently visited the litter (>30 times/day) and those that visited the litter less often (<10 times/day) in five bacterial families and seven genera. Notably, hens classified as visiting the litter less often, showed an increased abundance of Coriobacteriales , Peptococcales , Oribacterium and Lachnoclostridium taxa. Overall, this study offers new insights on the potential role of the microbiota in hen movement patterns.